2020
DOI: 10.1039/d0tc03153d
|View full text |Cite
|
Sign up to set email alerts
|

In situ observation of the magnetocaloric effect through neutron diffraction in the Tb(DCO2)3 and TbODCO3 frameworks

Abstract: Probing the magnetic structure of magnetocaloric materials in applied fields, can reveal detailed insight into the mechanism of magnetic refrigeration linking the magnetic states that form under applied magnetic fields...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…We anticipate that this likely stems from the ferromagnetic correlations within the paramagnetic phase of these materials as previously established for the ferromagnetic Ising chains in A(HCO 2 ) 3 (A = Tb and Ho) and BOHCO 3 (B = Tb and Dy) with the higher temperature scale in these hydroxides resulting from the stronger magnetic interactions within them. 14,21,33,47,49,50,54 Future studies of the hydroxides using modern neutron diffractometers to establish if they have magnetic diffuse scattering at these temperatures are needed to conrm this hypothesis.…”
Section: Magnetic Susceptibility and Magnetisationmentioning
confidence: 99%
“…We anticipate that this likely stems from the ferromagnetic correlations within the paramagnetic phase of these materials as previously established for the ferromagnetic Ising chains in A(HCO 2 ) 3 (A = Tb and Ho) and BOHCO 3 (B = Tb and Dy) with the higher temperature scale in these hydroxides resulting from the stronger magnetic interactions within them. 14,21,33,47,49,50,54 Future studies of the hydroxides using modern neutron diffractometers to establish if they have magnetic diffuse scattering at these temperatures are needed to conrm this hypothesis.…”
Section: Magnetic Susceptibility and Magnetisationmentioning
confidence: 99%
“…Consistent with the proposed origin of the magnetocaloric properties of Tb(HCO2)3, neutron diffraction studies have shown that the application of weak magnetic fields helps to stabilise the TIA phase; however, at fields above 0.2 T, the system transforms to a simple ferromagnetic state in which all chains are aligned. 16 It is well-known that diamagnetic impurities readily disrupt low-dimensional magnetic states, [17][18][19][20][21] so the unusual discovery of the TIA state in Tb(HCO2)3 raises the question of how this state responds to the introduction of such impurities, and in turn how diamagnetic impurities affect the magnetocaloric properties observed. In principle, replacing Tb 3+ with diamagnetic Y 3+ should be viable, given that the two cations have similar ionic radii: 1.095 and 1.075 Å for 9-coordinated Tb 3+ and Y 3+ , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the chains to readily align with a magnetic field when it is applied and antiferromagnetic correlations are suppressed, increasing their magnetisation rapidly under low applied fields and thereby enhancing their entropy changes. 26 Geometric frustration has long been identified as a way of improving the MCE performance of materials, including GGG itself, 27 due to it suppressing long-range magnetic order to much lower temperatures, which allows dense magnetic materials to be used leading to a higher ÀDS max m . Coupling this with ferromagnetic chains is, however, a newer concept and it is important to establish if such strong local magnetic order is always associated with enhancing paramagnetic magnetocalorics for high temperature applications.…”
Section: Introductionmentioning
confidence: 99%